The cry of the loon : a Samantha mystery - Steiner, Barbara A. (American Girl, 2009)
In June 1907, twelve-year-old Samantha looks forward to a happy summer with Nellie and her younger sisters at Grandmary's country home in the Adirondacks but a series of mysterious accidents on the property lead Samantha to suspect that someone is deliberately causing trouble.